EFEK MONOSODIUM GLUTAMAT TERHADAP GAMBARAN HISTOLOGI HEPAR TIKUS PUTIH (Rattus norvegicus) GALUR WISTAR - Shely Ayu Lestari; Dita Pratiwi Kusuma Wardani; Tantri Analisawati Sudarsono (Jurnal Media Analis Kesehatan, 2021)
Monosodium glutamate (MSG) is a sodium salt of glutamic acid that naturally comes from vegetable and animal protein functioned as a taste enhancer. So far, the use of MSG in various countries has increased by 1 g / day and can have an impact on cell damage to several organs. The purpose of this study was to find out the effects of MSG on the liver histology of Wistar white rats (Rattus norvegicus). This study used Posttest Only Control Group Design consisting of 4 groups, as control and MSG treatment doses of 5 g / kg BW, 10 g / kg BW, and 15 g / kg BW for 14 days orally. Each group consisted of 6 male white rats (Rattus norvegicus) aged 2-3 months with a weight of 200-250 grams in good health. A day after 14 days of treatment, the rats' liver organs were taken and preparations were made using the paraffin method. Data were analyzed using the Kruskal-Wallis test. The results of research showed that the control group looked normal, while the P1 group had 40.5 (40-43)% cell abnormalities and 52.5 (27-56)% cell abnormalities. The P3 group showed the most significant liver cell damage, namely 60 (59-62)%. The results of the Kruskal-Wallis test analysis showed a significant difference of p = 0.034 between cell abnormalities and the dose level of MSG (p-value 0.05). It can be concluded that MSG administration in stratified doses can cause liver cell damage in the form of degeneration and necrosis. Giving a dose of MSG 15 g / kg BW for 14 days showed the most significant liver cell damage at 60 (59-62)%.Keywords: Cell Abnormality, Liver, Monosodium Glutamate